Prevalence and Associated Factors of Hypertension among Women in Southern Ghana: Evidence from 2014 GDHS - Cyprian Issahaku Dorgbetor; Kwamena Sekyi Dickson; Edward Kwabena Ameyaw; Kenneth Setorwu Adde (International Journal of Hypertension)
Background. Hypertension, coupled with prehypertension and other hazards such as high blood pressure, is responsible for 8·5 million deaths from stroke, ischaemic heart disease, other vascular diseases, and renal disease worldwide. Hypertension is the fifth commonest cause of outpatient morbidity in Ghana. Some evidence have illustrated geographical variation in hypertension and it seems to have a heavy toll on women in southern Ghana compared to the north. This study seeks to determine the prevalence and associatedfactors of hypertension among women in southern Ghana using the most recent demographic and health survey (DHS) data set. Materials and Methods. This study used data of 5,662 women from the current DHS data from Ghana that was conducted in 2014. Data were extracted from the women’s file of the 2014 Ghana DHS. The outcome variable of this current study was hypertension and it was measured by blood pressure, according to guidelines of the Joint National Committee Seven (JNC7). Multivariable binary logistic regression analyses were performed to establish the factors associated with hypertension at the individual and community levels. Results. Prevalence of hypertension among women in southern Ghana was 16%. Women aged 40–44 years (aOR = 8.04, CI = 4.88–13.25) and 45–49 years (aOR = 13.20, CI = 7.96–21.89] had the highest odds of hypertension relative to women aged 15–19 years. Women with two births (aOR = 1.45, CI = 1.01–2.07) and those with three births (aOR = 1.47, CI = 1.01–2.15) had a higher likelihood of being hypertensive. Greater Accra women had higher odds (aOR = 1.35, CI = 1.02–1.79) of being hypertensive relative to the reference category, women from the Western region. Women of Guan ethnicity had a lesser likelihood (aOR = 0.54, CI = 0.29–0.98) of being hypertensive. Women who engaged in agriculture had the least likelihood (aOR = 0.72, CI = 0.52–0.99) of being classified hypertensive compared to unemployed women. Conclusion. This study has revealed the prevalence of hypertension among women in southern Ghana. The associated factors include age, parity, region, and occupation. As a result, existing interventions need to be appraised in the light of these factors. Of essence is the need for Ghana Health Service to implement wide-embracing health promotion initiatives that accommodate the nutritional, exercise, and lifestyle needs of women in southern Ghana. Having more children is associated with higher propensity of hypertension and consequently, women need to limit childbearing to reduce their chances of being hypertensive. It will also be advisable for women in the Greater Accra region to have frequent hypertension screening, as women in the region exhibited higher hypertension prospects.